On some generalization of normal operators on Hilbert space - H. Abood, Eiman; A. Al-loz, Mustafa (Iraqi Journal of Science, 2023)
In this paper we introduce a new class of operators on Hilbert space. Wecall the operators in this class, n,m- powers operators. We study this classof operators and give some of their basic properties.